2004
DOI: 10.1097/00001721-200406000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The use of recombinant activated factor VII for controlling life-threatening bleeding in Dengue Shock Syndrome

Abstract: To report the use of recombinant activated factor VII (rFVIIa) in controlling life-threatening bleeding episodes in patients with grades III and IV Dengue Hemorrhagic Fever (DHF), also known as Dengue Shock Syndrome. Fifteen patients (seven boys, eight girls), whose median age was 8 years, were enrolled in the study. They were divided into two groups. Group 1 included nine patients, mainly grade III, waiting for platelet concentrate, and group 2 included six patients, mainly grade IV, who had already received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…One of the two treatment options was assigned: a standard care or adjuvant rFVIIa in a dose of 80 mg/kg body weight [8,9]. This particular group had a representative age of patients who were most likely to be present with this condition, based on a study in Thailand [8]. The average weight of the patient was assumed to be 50 kg.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the two treatment options was assigned: a standard care or adjuvant rFVIIa in a dose of 80 mg/kg body weight [8,9]. This particular group had a representative age of patients who were most likely to be present with this condition, based on a study in Thailand [8]. The average weight of the patient was assumed to be 50 kg.…”
Section: Methodsmentioning
confidence: 99%
“…Effective response was defined as the condition in which the bleeding episode had completely stopped, and ineffective response as the condition in which the bleeding episode had worsened, remained unchanged, temporarily slowed, or had occurred at a new site [8].…”
Section: Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Chuansumrit et al have reported an observational study of 12 patients with DSS treated with rFVIIa for life-threatening bleeding episodes comprised by hematemesis, hematochezia, and hypermenorrhea. 24 Patient ages ranged from 1-14 years. rFVIIa was administered as bolus injections varying from 100-200 µg/kg/dose.…”
Section: Life-threatening Gi Bleeding In Dengue Shock Syndromementioning
confidence: 99%